Penyuluhan Kota Layak Anak Sebagai Wujud Sustainable Cities and Communities Melalui Pembuatan Mading di TK Islam Nurul Qur’an Depok - Rizkianti, Wardani; Putri, Sindy Yulia; Situmeang, Nurmasari; Chandra, Bastian; Salsabila, Fariezka Safa; Maulidah, Nurul Alya (Jurnal Pengabdian UNDIKMA, 2023)
This community service activity aims to increase the understanding of teachers and parents of Nurul Qur’an Islamic Kindergarten students about child-friendly cities as a form of effort to achieve sustainable cities and communities (SDGs 11). This service was implemented using counseling, which consists of lectures, demonstrations, and small group discussions. The instrument for evaluating this activity used questionnaires and then analyzed descriptively. The results of this service showed the increased understanding of teachers and parents of Nurul Qur’an Islamic Kindergarten students regarding the fulfillment of children’s needs, which included the right to obtain identity, get an education, play, get protection, recreation, get food, get health insurance, and get national status. Counseling on child-friendly cities through mading (wall magazine) also increased the awareness of parents, especially mothers, that sustainable cities and communities as a global development agenda (SDGs) start from the smallest unit, namely the family.